Pengaruh Pengungkapan ESG dan Ketepatan Waktu Pelaporan Keuangan Terhadap Nilai Perusahaan Melalui Struktur Modal (Sektor Barang Konsumen Primer di BEI, 2022–2024): Primary Consumer Goods Sector on The Indonesia Stock Exchange, 2022-2024 - Annisa Ramadhini Salsabila; Ihsan Nasihin; Dhea Imroatul Fatihah (Sanskara Akuntansi dan Keuangan, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) disclosure and financial reporting timeliness on firm value, with capital structure as a mediating variable in primary consumer goods companies listed on the Indonesia Stock Exchange during the 2022-2024 period. This research employs a quantitative approach with an explanatory method. The sample consists of 33 companies with a total of 99 observations, analyzed using multiple linear regression and Baron and Kenny mediation tests through SPSS. The results indicate that ESG disclosure has a significant negative effect on firm value, while financial reporting timeliness has no significant effect on firm value. ESG disclosure does not affect capital structure, whereas financial reporting timeliness has a significant effect on capital structure. Capital structure significantly affects firm value and only mediates the relationship between financial reporting timeliness and firm value, but does not mediate the relationship between ESG disclosure and firm value. The study concludes that the role of ESG in enhancing firm value is has not yet optimal, while reporting timeliness plays a more significant role through financing mechanisms. The implication of this study suggests that companies need to improve the quality of ESG disclosure substantively and maintain timely financial reporting to enhance investor confidence